THE RESEARCH OF GENE POLYMORPHISM OF GLUTATHIONE-S-TRANSFERASE FAMILY ASSOCIATION: GSTM1, GSTТ1 AND GSTР1 WITH THE DEVELOPMENT OF BRONCHOPULMONARY DYSPLASIA AND NECESSITY IN RESPIRATORY SUPPORT - O.M. Kovalyova; V.I. Pokhylk; Z.I. Rossokha; N.G. Gorovenko; Y.O. Goncharova (Bukovynian State Medical University, 2019)
Bronchopulmonary dysplasia (BPD) is the one of most widespread complications of preterm delivery. GST gene is known to have an influence on the lungs development. The aim of this research is the investigation of association between the polymorphism of gene of glutathione-S-transferase family and the BPD development, the difficulty of clinical course and the necessity in respiratory support. 21 children with BPD and 70 of premature babies without BPD were investigated. The influence of the genetic determinant of indicators which characterize the respiratory support for premature babies was analyzed such as: the frequency of MV and CPAP usage, oxygen therapy, MV duration, CPAP duration, maximal peak inspiratory pressure (PIP). During the research the significant influence of gene polymorphism GSTT1 GSTM1 GSTP1for the BPD development and its heavy course wasn't revealed. The significant longer duration of MV in children with deletion polymorphism GSTТ1 and AG, GG gene genotype GSTР1and the presence of the combination of genotypes in children: GSTТ1 «-»/ GSTМ1 «-», GSTТ1 «-»/GSTР1 (АG+GG) were determined. Further investigations for optimization of MV mode taking into account the genetic peculiarities of patients are needed.